2010
DOI: 10.1007/s10384-010-0881-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timolol-related ophthalmic solutions on cultured human conjunctival cells

Abstract: Compared with Timoptol and Timoptol XE, Rysmon TG and Timabak showed milder toxicity on human conjunctival cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition, it was reported that gelling temperature was affected not only by the pluronic F127 concentration but also by the proportions of combined pluronic F127 and pluronic F68 [ 49 ]. Moreover, temperature-sensitive MC and pH-sensitive Carbopol are also frequently used as agents when combining two ISGs [ 50 , 51 ]. We prepared the Tra-NP-incorporated ISNGs with the combination of pluronic F127 and MC, pluronic 68, Carbopol, and determined the concentration of the ISG base following previous reports for ISG systems [ 32 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that gelling temperature was affected not only by the pluronic F127 concentration but also by the proportions of combined pluronic F127 and pluronic F68 [ 49 ]. Moreover, temperature-sensitive MC and pH-sensitive Carbopol are also frequently used as agents when combining two ISGs [ 50 , 51 ]. We prepared the Tra-NP-incorporated ISNGs with the combination of pluronic F127 and MC, pluronic 68, Carbopol, and determined the concentration of the ISG base following previous reports for ISG systems [ 32 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal damage was observed after the treatment with nTRA-Car/F127-L ( Figure 4 ). It has been reported that pH-sensitive gels are more toxic in comparison to temperature-sensitive gels, and pH-sensitive gels easily damage conjunctival cells [ 51 ]. Therefore, this result suggested that the corneal toxicity of nTRA-Car/F127 was caused by Carbopol and pH-sensitive gels, and caution is necessary with long-term use of nTRA-Car/F127-H.…”
Section: Discussionmentioning
confidence: 99%
“…An in situ gelling system seems to be a good candidate for prolonging the drug residence time and enhancing absorption into the ocular surface (Wu et al, 2019;Yadav et al, 2019). Three systems, thermosensitive, ion-activated (Rupenthal et al, 2011) and pH-sensitive (Bawa et al, 2009), have been introduced, and the thermosensitive type systems widely used in comparison with other two types, since they involve less ocular stimulation (Kawase et al, 2010). Various polymers, such as methylcellulose (MC), alginic acid, gellan gum, chitosan, xyloglucan and pectin, can potentially be used for in situ gelling systems (Madan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In-situ forming gels show sol-to-gel transitions in response to one or two or even more combinations of stimuli, including UV irradiation, temperature, and pH changes, solvent exchange (Al-Tahami and Singh, 2007). Based on stimuli, in situ gel can be divided into in situ gel activated ions (Rupenthal et al, 2011), thermosensitive and sensitive to pH from all three in situ the gel in situ thermosensitive gel has a higher safety (Kawase et al, 2010). In situ, this thermosensitive gel will undergo the process of transitioning from sole to gel during heating or cooling; it can occur due to changes in intermolecular (Ruel-Gariépy and Leroux, 2004).…”
Section: Introductionmentioning
confidence: 99%